Brief Research Report: Ebola Virus Differentially Infects Human Iris and Retinal Pigment Epithelial Cells - Todd, Shawn; Ma, Yuefang; Ashander, Liam M.; Appukuttan, Binoy; Michael, Michael Z.; Blenkinsop, Timothy A.; Yeh, Steven; Marsh, Glenn A.; Smith, Justine R. (Frontiers in Virology, 2022)
Uveitis is a common manifestation of post-Ebola syndrome, associated with persistence of Zaire ebolavirus (EBOV) inside the eye. The iris and retinal pigment epithelia are key components of the blood-ocular barriers, but have the capacity to act as hosts for microorganisms. We investigated the ability of EBOV to productively infect these cell populations. Donor-matched human iris and retinal pigment epithelial isolates (n = 5) were infected with EBOV at a multiplicity of infection of 1 for up to 72 hours. Parallel cultures were infected with Reston ebolavirus (RESTV) or Zika virus (ZIKV), or held uninfected under the same conditions. Viral RNA load by RT-qPCR on total cellular RNA, cytoimmunofluorescence, and assays of 50% tissue culture infected dose of culture supernatant showed that both iris and retinal pigment epithelial isolates were permissive to infection, and supported replication and release of EBOV, as well as RESTV and ZIKV. However, in comparison to cells isolated from iris, those from retina demonstrated obvious EBOV-induced cytopathic effect, had higher intracellular EBOV RNA loads, expressed intracellular EBOV protein more widely, and released EBOV at higher titer. Comparable results were obtained for isolates infected with RESTV and ZIKV. Consistent with observations of retinal pigment epithelial scars in Ebola survivors, our results suggest that an early event in post-Ebola uveitis is infection of the retinal pigment epithelium. Relative susceptibility of retinal pigment epithelial cells to infection with RESTV and ZIKV, as well as EBOV, implies this phenomenon may relate to a cell-specific attribute, such as high phagocytic activity.